SOJA-HORTALIÇA EM CULTIVO ORGÂNICO NA REGIÃO ECÓTONO CERRADOPANTANAL - RIBERA, Laura Matos; SAKISSAKA, Roberto Carlos Seiji; RAMIRES, Lucas Richard da Silva; ANDRADE, Dener Coelho de; CARDOSO, Reginaldo de Moraes; SILVA, Maiele Leandro da (ANAIS DO ENIC, 2018)
-